GENDER ISSUES IN SCHOOL AND CLASSROOM PRACTICE: A CASE STUDY OF PONDICHERRY - R.M, AMRUTHRAJ (THE PRIMARY TEACHER, 2013)
Increasing concern has been expressed about the role of the formal education system in reproducing gender differences and inequalities. Research studies indicate that issues that impact girls’ education include discrimination against girls in classrooms, interaction between boys and girls, effect of gender on education and other submerged hidden curriculum. The present paper focuses on gender issues prevailing in the school settings in Pondicherry (Puducherry). The analysis shows how classroom practices, teacher attitudes and classroom structure disaggregate boys and girls. It also put forward few suggestions for a gender sensitive education